1966
DOI: 10.3133/pp543b
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic effects of the earthquake of March 27, 1964 in the Martin-Bering Rivers area, Alaska

Abstract: The Alaska earthquake of March 27, 1964, caused widespread geomorphic changes in the Martin-Bering Rivers area-900 square miles of uninhabited mountains, alluvial flatlands, and marshes north of the Gulf of Alaska, and east of the Copper River. This area is at lat 60°30' N. and long 144°22' W., 32 miles east of Cordova, and approximately 130 miles east-southeast of the epicenter of the earthquake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The most comprehensive and recent publication by Podolskiy et al () reports 22 historical cases of earthquake‐triggered snow avalanches that occurred between 1899 and 2010 in cold Arctic regions and highly elevated mountainous terrains (e.g., the Himalayas). Important cases include rock and ice avalanches in the Chugach Mountains triggered by the 1964 Alaska earthquake (Post, ; Tuthill & Laird, ); the 1,580 large landslides triggered by the 2002 Denali earthquake over the glaciated terrain of Alaska (Gorum et al, ; Jibson et al, ); the 1,448 snowmelt‐induced landslides following the 2004 Mid‐Niigata prefecture earthquake (Akiyama et al, ), and the long runout landslides triggered over snow during the 2011 Nagano prefecture earthquake in Japan (Has et al, ; Yamasaki et al, ).…”
Section: Coseismic Landslidesmentioning
confidence: 99%
“…The most comprehensive and recent publication by Podolskiy et al () reports 22 historical cases of earthquake‐triggered snow avalanches that occurred between 1899 and 2010 in cold Arctic regions and highly elevated mountainous terrains (e.g., the Himalayas). Important cases include rock and ice avalanches in the Chugach Mountains triggered by the 1964 Alaska earthquake (Post, ; Tuthill & Laird, ); the 1,580 large landslides triggered by the 2002 Denali earthquake over the glaciated terrain of Alaska (Gorum et al, ; Jibson et al, ); the 1,448 snowmelt‐induced landslides following the 2004 Mid‐Niigata prefecture earthquake (Akiyama et al, ), and the long runout landslides triggered over snow during the 2011 Nagano prefecture earthquake in Japan (Has et al, ; Yamasaki et al, ).…”
Section: Coseismic Landslidesmentioning
confidence: 99%
“…The earthquake of 27 March 1964, that devastated Anchorage and other towns such as Whittier, also affected the “Sioux Glacier” area (Grantz and others, 1964; Post, 1965, 1967; Tuthill and Laird, 1966). The glacier is located approximately 200 km south-east of the epicenter of the initial shock; Anchorage is 125 km west of the epicenter.…”
Section: Characteristics Of the Debris Slidementioning
confidence: 99%
“…Numerous publications have resulted from the first 3 years of glacial research, including those by Reid and Clayton (1963), Tuthill (1963, 1966), Clayton (1964), Laird and Tuthill (1964), Reid and Callender (1965), Tuthill and Laird (1966), and Reid (1967). Other authors have reported the existence of the debris slide on “Sioux Glacier” subsequent to the Good Friday earthquake (Grantz and others, 1964; Post, 1965, 1967; Ragle and others, 1965).…”
Section: Introductionmentioning
confidence: 99%